Le premier Italien au cap Nord : le père Francesco Negri (1663-1666) - Grillo Orlandini, Alessandra (Presses universitaires de Rennes, 2019)
Francesco Negri, a priest from the town of Ravenna, was the first Italian traveller to reach the North Pole in 1666. His travel stories, “Viaggio Settentrionale”, were very innovative considering the period in which he wrote them and especially considering the type of travel he wrote about. Francesco Negri was the only traveller who had stayed in Nordic countries for a period of three years, travelling the length and breadth of the interior regions, as well as the coast and making contact with Laplanders whose culture charmed the Italian priest, as he was already passionate and curious about the diversity of the world. Composed of eight letters, his travel writing describes Lapland and the customs of its inhabitants, with several illustrations and many quotations taken from classical Latin authors, as well as from Nordic writers who were contemporaries of Negri. These quotes testify to the thoroughness of the research carried out by the priest, both when he was already on site (where he learned several facts about the local culture through Norwegian priests who gave him accommodation) and after he returned to Italy.